IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI BUDAYA SEKOLAH - Anggraini, Devi; Purnomo, Heru (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
This study aims to describe the implementation of character education through school culture and identify the influencing factors, both supporting and constraining its implementation. The approach used in this study is descriptive qualitative. Data were collected through direct observation, in-depth interviews, and documentation studies. Data analysis was carried out through the stages of data collection, reduction, presentation, and drawing conclusions. The results of the study indicate that character values ​​are instilled through learning activities, including by getting students used to praying before and after lessons, training problem-solving skills individually and in groups, encouraging students to actively ask questions and express opinions, and completing tasks independently. In addition, character formation is also realized through routine activities and role models, such as flag ceremonies, morning assembly, literacy programs, religious literacy, gymnastics activities, congregational Dzuhur prayers, and infaq activities. The implementation of character education based on school culture is influenced by a number of factors. The obstacles faced include low compliance of some students to teacher directions, weak personal awareness of students regarding the importance of character values, and lack of interest in literacy activities. This situation suggests the need for a more individual, sustainable, and creatively and attractively packaged coaching approach. On the other hand, the success of this program also has a number of supporting factors, including high commitment from teachers, enthusiasm and active involvement of students, parental involvement, and the availability of adequate supporting facilities. Collaboration between schools, students, and parents is a crucial aspect in realizing school culture as an effective means of forming students' characters in a complete and sustainable manner.